2023
DOI: 10.1055/s-0042-1758862
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between heart rate variability and cognitive decline? A cross-sectional study on patients with mild cognitive impairment and cognitively healthy controls

Abstract: Background Given that, up to date, there is no effective strategy to treat dementia, a timely start of interventions in a prodromal stage such as mild cognitive impairment (MCI) is considered an important option to lower the overall societal burden. Although autonomic functions have been related to cognitive performance, both aspects have rarely been studied simultaneously in MCI. Objective The aim of the present study was to investigate cardiac autonomic control in older adults with and without MCI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Although the types of stimuli were not directly comparable to our study protocol, these previous studies suggested that older people with MCI were likely to have decreased cardiac reactivity in association with poorer performances, which was not consistent with our funding in the current study. Grässler et al (2023) reported the significant decreases in RMSSD from resting to a Stroop task in people with MCI as compared with healthy control, indicating the vagal withdrawal in people with MCI. However, our results did not show the significant effects of cognitive impairment on autonomic control.…”
Section: Discussionmentioning
confidence: 95%
“…Although the types of stimuli were not directly comparable to our study protocol, these previous studies suggested that older people with MCI were likely to have decreased cardiac reactivity in association with poorer performances, which was not consistent with our funding in the current study. Grässler et al (2023) reported the significant decreases in RMSSD from resting to a Stroop task in people with MCI as compared with healthy control, indicating the vagal withdrawal in people with MCI. However, our results did not show the significant effects of cognitive impairment on autonomic control.…”
Section: Discussionmentioning
confidence: 95%
“…Some good examples mentioned here are using nonlinear measures for a proper characterization of EEG 94 , and with a good choice of ML model (with proper internal and external validation, plus taking care of dimensionality problem), they could offer a solution for clinical recognition of prodromal phase of AD. Besides, it is already emerging that MCI (and particularly aMCI) could be detected based on another electrophysiological signal, namely electrocardiogram (ECG) from which heart rate variability (HRV) can be extracted and is a marker of autonomic nervous system 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Amnestic MCI (aMCI) is considered to be a prodromal phase for AD 3,5 , the other one is correlated to different forms of dementias, like vascular dementia or levy body dementias 14 . Half of the people who exhibit aMCI are converted to AD (on average 3 years after the first MCI identification, as in 15 ). Consequently, aMCI is considered to be a risk for AD and sometimes is called MCI-prodromal-to-dementia 3,17,18 .…”
Section: Introductionmentioning
confidence: 99%